2021
DOI: 10.1007/s12559-020-09801-w
|View full text |Cite
|
Sign up to set email alerts
|

An Agent-Based Modeling of COVID-19: Validation, Analysis, and Recommendations

Abstract: The coronavirus disease 2019 (COVID-19) has resulted in an ongoing pandemic worldwide. Countries have adopted non-pharmaceutical interventions (NPI) to slow down the spread. This study proposes an agent-based model that simulates the spread of COVID-19 among the inhabitants of a city. The agent-based model can be accommodated for any location by integrating parameters specific to the city. The simulation gives the number of total COVID-19 cases. Considering each person as an agent susceptible to COVID-19, the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 29 publications
0
62
0
Order By: Relevance
“…Three of the 15 studies had a high risk of bias due to the lack of use of empirical distributions for variables, the limited number of scenarios analysed and insufficient transparency regarding reporting of the model. 11 20 21 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of the 15 studies had a high risk of bias due to the lack of use of empirical distributions for variables, the limited number of scenarios analysed and insufficient transparency regarding reporting of the model. 11 20 21 …”
Section: Resultsmentioning
confidence: 99%
“… 15 Another model-based study determined that 60% adoption rate of a CTA could result in an R below 1.0. 11 In one study, adoption rate of 53% resulted in a 47% reduction in R when the complete household of an individual with a positive test result is advised to be quarantined. 14 The last study looking at effect of CTA on R showed that only at 60% adoption rate of the app a significant beneficial effect on R would become apparent.…”
Section: Resultsmentioning
confidence: 99%
“…DCTA availability and accessibility must be equitable, and they should not be used in a discriminatory way [ 52 , 56 , 66 , 87 , 175 ]. This is important not only from a human rights perspective but also from an effectiveness perspective because the success of a DCTA depends on factors such as user penetration within the general population [ 88 ] and in high-risk population groups [ 15 , 89 ]. The IDCTA should be disseminated free of charge, so it is accessible by all societal groups but, in particular, those disproportionately affected by COVID-19 such as older adults, people of lower socioeconomic class, and ethnic minorities [ 51 , 52 , 56 , 61 , 90 , 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many ABMs for COVID-19 are in the scale of several hundred agents [78][79][80][81][82][83] to tens of thousands of agents [37,84,85]. Fewer studies have over 100,000 agents [86], and only a paucity of studies has a number of agents that is about equal (eg, the model of Hoertel and colleagues [87] used 500,000 agents) or greater than (eg, one million agents in a February 2021 simulation of Bogota) in this study [38,87,88].…”
Section: Related Work: the Scale Of Agent-based Models For Covid-19mentioning
confidence: 99%